2021
DOI: 10.3389/phrs.2021.1604061
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Epidemiologic, Diagnostic and Treatment Approaches of COVID-19: What do We Know?

Abstract: Background: In late December 2019, a new infectious respiratory disease (COVID-19) was reported in a number of patients with a history of exposure to the Huanan seafood market in China. The World Health Organization officially announced the COVID-19 pandemic on March 11, 2020. Here, we provided an overview of the epidemiologic, diagnostic and treatment approaches associated with COVID-19.Methods: We reviewed the publications indexed in major biomedical databases by December 20, 2020 or earlier (updated on May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 163 publications
(193 reference statements)
0
3
0
1
Order By: Relevance
“…This variability in the R 0 estimates is due to several factors, including the model used for its estimation, public health interventions to control the pandemic, level of implementation of precautionary measures (e.g., travel restrictions, social distancing), and population size/density [12][13][14]. The case fatality rate (CFR) for COVID-19 ranges from 0.87% to 2.79% in different countries, with a global CFR estimate of approximately 2.07% [2,15]. Moreover, the morbidity and mortality rate of COVID-19 is higher among individuals with comorbid conditions and among older individuals [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This variability in the R 0 estimates is due to several factors, including the model used for its estimation, public health interventions to control the pandemic, level of implementation of precautionary measures (e.g., travel restrictions, social distancing), and population size/density [12][13][14]. The case fatality rate (CFR) for COVID-19 ranges from 0.87% to 2.79% in different countries, with a global CFR estimate of approximately 2.07% [2,15]. Moreover, the morbidity and mortality rate of COVID-19 is higher among individuals with comorbid conditions and among older individuals [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Carissa F. Etienne expresó: "Las vacunas salvan vidas y deben mantenerse incluso durante la pandemia de COVID-19. Las personas más vulnerables no deben sufrir las consecuencias de no recibir las vacunas que necesitan" (1), por estas razones los múltiples avances científicos para controlar la pandemia de COVID-19 están relacionado con investigación de vacunas seguras contra el SARS-CoV-2, que hasta el 9 de agosto de 2023 se han administrado 13.492 millones de dosis de vacunas, pero aún se necesitan nuevos enfoques profilácticos y terapéuticos (25)(26)(27)(28)(29), por lo tanto, debido a la falta de un tratamiento curativo definitivo para el COVID-19, la solución más eficaz es el diagnóstico oportuno y la difusión de las medidas preventivas de la enfermedad (30).…”
Section: Discussionunclassified
“…Scientists have been working in the quest for possible preventive and therapeutic methods. 5 7 It is reported that eight vaccines were approved for full use for the first time, while the other six vaccines got approval for limited use against COVID-19. 7 9 However, the emergence of SARS-CoV-2 variants led to increased transmission and resistance, which is associated with antibody escape from the virus spike epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have been working in the quest for possible preventive and therapeutic methods. It is reported that eight vaccines were approved for full use for the first time, while the other six vaccines got approval for limited use against COVID-19. However, the emergence of SARS-CoV-2 variants led to increased transmission and resistance, which is associated with antibody escape from the virus spike epitopes . Currently, there is only one specific oral antiviral agent against SARS-CoV-2, namely, molnupiravir.…”
Section: Introductionmentioning
confidence: 99%